A framework for mobile interactive language learning using near field communication (NFC) technology - Yahaya Garba Shawai
Technology mediated learning such as Near Field Communication (NFC) enables and supports interactive learning that integrates digital learning characteristics. NFC tags interact with application by touching the tagged objects with mobile devices. The present research explored the potentials of interactive technology to support interactive teaching and learning process. The aim of the research is to propose a framework for mobile language learning and to develop an interactive teaching and learning system using NFC technology, as well as to evaluate the proposed framework and the system being developed. The present research adopted and improved "Mobile learning framework for lifelong learning" to support the development of an interactive mobile learning application. The application is interactive and operated in game-like environments in which learners gain knowledge through exploration. The evaluation Forms were distributed to seven (7) experts who have research interest in e-leaming at Universiti Sultan Zainal Abidin (UNISZA) and Universiti Malaysia Terengganu (UMT). In addition, two sets of questionnaires (Pre and post) were also distributed to 170 international postgraduate students (138 males and 32 females) of UNISZA and UMT by random. The data was then analyzed using frequency distribution of descriptive statistics. The result of the expert evaluation shows that 100% of them are satisfied with the added features in the framework. Apart from that, 86% agreed that the connections among features and the process flow in the framework are logical and practical. In terms of the students' response, they agreed that the traditional way of learning Malay language is not as efficient as using mobile device. 87% pointed that it is difficult to find the required information if the traditional approach is used. 58% of the respondents agreed that the system is user friendly and easy to use. Meanwhile, 68% mentioned that the user will not take longer time to learn the language if the developed system is used to assist the learning process. In conclusion, international students are encouraged to use the developed system as an additional support tool in learning Malay language.